Implementasi Aplikasi EPANET Dalam Evaluasi Pipa Jaringan Distribusi Air Bersih PDAM Kolaka - Romy Talanipa; Tryantini Sundi Putri; Fathur Rahman Rustan; Andi Tria Yulianti (Faculty of Computer Science, University of Jember, 2022)
The need for raw water for various reasons, particularly clean water for households, public areas, and industry, will continue to rise as the world's population grows and the pace of growth in various fields accelerates. However, because the existing supply of clean water infrastructure is still limited, it has not been able to cover all of the country's water needs. Residents in Latambaga District, Kolaka Regency, are likewise concerned about the lack of safe water. Although the area has adequate water sources (river water) and a distribution network that distributes clean water to the population, the issue is getting water from these water sources to areas where there isn't an optimal clean water distribution network so that it can be used by the community population. As a result, it is required to assess PDAM Kolaka's clean water distribution network by employing the EPANET program application in its analysis. The findings of the pipeline network evaluation using the EPANET 2.0 application, the diameter of the pipes used in the evaluation, pipes with a diameter of 1